A Comparative Analysis of Short Term Postoperative Complications in Outpatient vs. Inpatient Total Ankle Arthroplasty. Issue 3 (14th September 2018) - Shah, Ashish; DeBell, Henry; Tedder, Chandler; Pinter, Zachariah; Naranje, Sameer; McGee, Andrew; Paul, Kyle; Huntley, Samuel; Archie, Adam
Category: Ankle Introduction/Purpose: Ankle arthritis is a potentially debilitating disease with approximately 50, 000 cases diagnosed annually. Once conservative management fails, surgical options for these patients include total ankle arthroplasty (TAA) and ankle arthrodesis. Younger, more active patients may prefer TAA as it may allow better ankle mobility compared to ankle arthrodesis. TAA has historically been performed in the inpatient setting with a one- to two-night postoperative hospital stay. Outpatient surgeries are gaining popularity due to their cost effectiveness, decreased length of hospital stay, and convenience. Therefore, it is important to evaluate the safety of specific procedures in the outpatient setting compared to the inpatient setting. This study evaluates the complication rates in inpatient vs. outpatient TAA. Methods: Our team conducted a retrospective analysis of data from 591 patients receiving inpatient and outpatient TAA from the NSQIP database. This database contains de-identified patient data and allows retrospective analyses to be performed based on data they have extracted from over 400 hospitals. Demographic information was recorded including age, sex, weight, height, and race. Thirty-day postoperative complication rates were compared between 66 outpatients and 535 inpatients. Frequencies of the following complications were analyzed: wound complications, pneumonia, hematologic complications (pulmonary embolism and deep vein thrombosis), renal failure, stroke, and return to the operating room within 30 days. The inpatient and outpatient groups were compared using chi-squared tests for categorical variables and Wilcoxon rank-sum tests for continuous variables. Results: 591 total patients were identified that underwent TAA. 66 patients (11.1%) were treated as outpatients and 525 (88.8%) as inpatients. Inpatient TAA had a significantly higher mean operation time (161 min vs 148 min) and a significant difference in length of total hospital stay (2.3 days vs 1.1 days). Inpatients had higher rates of superficial incisional surgical site infection (SSI) (0.57% vs 0%), deep SSI (0.19 % vs 0%), organ/space SSI (0.19% vs 0%), pneumonia (0.38% vs 0%), and return to the operating room (0.76% to 0%). However, no significant differences were found in complication rates between inpatient and outpatient groups. There were no occurrences of acute renal failure, wound disruption, pulmonary embolism, stroke, or DVT/thrombophlebitis for inpatients or outpatients. Conclusion: We found no significant difference between inpatient vs. outpatient TAA. Incidental differences we found were that inpatients were significantly more likely to be older in age, diagnosed with diabetes, and inpatients had longer operative times. Our results suggest that inpatients are more likely, but not significantly, to have a higher occurrence of complications and return to the OR. Therefore, this study suggests that outpatient TAA is safe and may be a superior option for the correct patient population. Further investigation is warranted to verify these conclusions.